The Effectiveness of The Six Tier Diagnostic Test (STDT) Instrument in Viewed from Empirical Validity to Identify Student's Misconceptions in Chemical Equilibrium Materials - Suyono Suyono; Khurrotul Aini; I Gusti Made Sanjaya (IJORER : International Journal of Recent Educational Research, 2023)
Objective: Students are said to understand the concept comprehensively if they master the concepts from dimensions of ontology, epistemology, and axiology. One of the topics that still needs to be clarified is chemical equilibrium. Therefore, it is necessary to develop instruments to diagnose conceptions about the chemical concepts taught. The STDT is one of the instruments that will be developed by researchers, which contains three scientific questions to identify misconceptions in chemical equilibrium. Method: This development research used the ADDIE model. The instrument's effectiveness refers to the empirical validity after applying the STDT instrument. The effectiveness of the STDT instrument was obtained through the correlation of misconceptions experienced by students with the level of difficulty of the items. The STDT instrument was applied to 86 students. Results: The percentage of students who experienced the highest misconceptions occurred in the chemical equilibrium section of the equilibrium shift due to the influence of a catalyst. In each item of questions, most students need more knowledge or knowledge. The composition of the difficulty of these items should be considered from the start of the instrument's preparation. In the developed STDT instrument, the item difficulty obtained from empirical trials on students did not meet the ideal conditions for the composition of the item difficulty level. Novelty: The resulting instrument for detecting misconceptions. It is a tier diagnostic test that is integrated with three scientific questions.